Constructing and development of the psycho-computing traits scale: a psychometric analysis of computer users and students in the field of computer science - Shoeb Saleh; Rommel AlAli (Cogent Social Sciences)
Psycho-computing refers to the study of the interaction between humans and computers, with the aim of understanding how people use computer applications in line with their needs and improving their experience. To achieve this goal, it is necessary to have a set of observable and measurable indicators of the behavioral practices of computer application users. Accordingly, a psycho-computing traits scale was developed that extracts six main dimensions of the behavioral practices of computer users and computer science students. To ensure the validity and reliability of the scale, it was applied to a survey sample of 150 students. Subsequently, the final version of the scale was applied to an experimental sample of 722 students to verify its psychometric properties. The results of the study indicate that the psycho-computing traits scale exhibits sound psychometric properties in terms of construct validity, as evidenced by the results of the Rasch model assumptions for the data obtained from its application. Moreover, the confirmatory factor analysis results demonstrate that the goodness of fit indicators align with the main dimensions of the scale. The study’s findings also suggest that the psycho-computing traits scale exhibits high reliability, as indicated by the results of the Rasch model for both person and item reliability. Therefore, the scale can be considered a valid tool for evaluating the psycho-computing traits of computer users and computer science students.